Penguatan Literasi Hukum Lintas Negara Bagi Masyarakat Perbatasan (Di Kawasan Perbatasan Indonesia–Papua Nugini, Sota Merauke) - Yuldiana Zesa Azis; Marlyn Jane Alputila; Emiliana Bernadina Rahail; Nasri Wijaya; Ahmad Ali Muddin (Astha Grafika, 2026)
The Indonesia–Papua New Guinea border area in Sota District, Merauke Regency is characterized by high cross-border activities that require adequate legal understanding among the community. The research problem lies in the low level of legal literacy regarding immigration procedures, travel documents, and citizens’ rights and obligations. This study aims to improve legal literacy through cross-border legal education programs. The research method employs a participatory approach through legal counseling, interactive discussions, case studies, and the distribution of educational materials such as guidebooks and legal information sheets. The results indicate an increase in community understanding of cross-border legal regulations, the importance of compliance with laws, and applicable procedures in cross-border activities. Furthermore, the educational approach enhances legal awareness and strengthens the legal culture of the border community. In conclusion, cross-border legal education programs are effective in improving legal literacy and should be implemented sustainably through collaboration among stakeholders.